2013
DOI: 10.1177/1721727x1301100116
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitro-Inductionof Type II Collagen-Specific Immune Tolerance in BALB/C Mice

Abstract: Type II collagen (CII) protein is the main component of hyaline cartilage. The clinical importance of CII in arthritis, aging, and osteoarthritis is significant, but its ability to induce specific immune tolerance has not been extensively studied previously. We have recently proven that CII is capable of inducing Anterior Chamber Associated Immune Deviation (ACAID) when injected into the eye. Here, we hypothesized that ACAID-mediated tolerance could be induced in Balb/c mice that receive an intravenous adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…We have previously shown the induction of specific immune tolerance in Balb/c mice through injection of CII into the AC of the eye or the intravenous injection of in vitro ‐generated ACAID APCs specific to CII . In the present study, we extended our observations to C57BL/6 and DBA/1 mice, in which arthritis could be potentially induced.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We have previously shown the induction of specific immune tolerance in Balb/c mice through injection of CII into the AC of the eye or the intravenous injection of in vitro ‐generated ACAID APCs specific to CII . In the present study, we extended our observations to C57BL/6 and DBA/1 mice, in which arthritis could be potentially induced.…”
Section: Discussionsupporting
confidence: 58%
“…We have recently shown that CII could induce peripheral tolerance in Balb/c mice via the AC injection of CII or the intravenous injection of in vitro ‐generated CII‐specific ACAID APCs . Whether CII could induce ACAID in the arthritis‐prone DBA/1 or C57BL/6 mice remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation